Knowledge and application of bioethical principles in postgraduate Dental Students - Morales, Gabriela; Ramadán, Ramiro; Alvear D., Susana; Sánchez-del-Hierro, Galo (Acta Bioethica, 2021)
Bioethics has been formally added, since 2008, to the curricula of dentistry courses in Ecuador. Documents have also been created that govern the ethical actions of the dentist in the face of different dilemmas that may arise during their clinical activity. This research seeks to describe the level of knowledge and application of bioethical principles in oral health professionals. A quantitative, descriptive and cross-sectional research method was used, by means of a structured survey, applied to postgraduate students in the dental area. The data were processed and analyzed in a descriptive and correlational manner. The results obtained highlighted the presence of five levels of knowledge of bioethical principles. Among these, in the groups with the highest percentage of knowledge about bioethical principles, the application of the principle of non-maleficence in their clinical practice was highlighted. Lack of knowledge about the theory was revealed: many are unaware of the basic bioethical principles of the correct action of the oral health professional. However, a growing change has been demonstrated with regard to the application of these principles.